The effects and durability of an 8-week dynamic neuromuscular stabilization program on balance and coordination in adult males with intellectual disabilities: a randomized controlled trial - Hamed Babagoltabar-Samakoush; Behnoosh Aminikhah; Saeid Bahiraei (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background Individuals with intellectual disabilities (IDs) often exhibit lower levels of physical fitness, including reduced balance and neuromuscular coordination, compared to the general population. Dynamic neuromuscular stabilization (DNS) training has been proposed as a potential intervention to improve physical fitness in this population, but its effectiveness and durability on specific fitness components remain underexplored. This study aims to investigate the effects and durability of an 8-week DNS program on balance and coordination in adult males with IDs. Methods Thirty-one participants were randomly assigned to either an intervention group (n = 16) or a control group (n = 15). Balance and neuromuscular coordination were assessed at baseline, immediately after the intervention, and two months post-intervention using the Balance Error Scoring System (BESS), walking forward heel-to-toe test, and bilateral coordination test. The intervention group participated in the DNS training program for 8 weeks, with three sessions per week, while the control group maintained their usual activities. Results Analysis of the outcome measures revealed significant time, group, and time-group interaction effects. Post-hoc analyses indicated that the DNS group showed significantly greater improvements in BESS scores and coordination compared to the control group (p < 0.01). These improvements were maintained at the two-month follow-up assessment. Conclusion This study provides robust evidence that DNS exercises can significantly enhance balance and neuromuscular coordination in middle-aged males with IDs, with improvements maintained over two months post-training. However, the exclusive focus on male participants limits the extrapolation of these findings to the broader population of individuals with IDs, particularly females. Future investigations should aim to address this limitation by including more diverse samples to advance the generalizability and applicability of DNS-based interventions in this field. Trial registration RTC, Registered prospectively at the registry of the clinical trial (UMIN000053560), Registered on 07/02/2024.